Measurement of Friction Losses of Electro-Pneumatical Valves with Industrial Devices - Sipos, Kristóf; Tóth, János (International Journal of Engineering and Management Sciences, 2017)
The pneumatic devices are frequently used in several fields of the industry but the losses and pressure drops of the pneumatic system are not really investigated. These losses can cause great property damages during long uptime because the compressed air is a quite expensive energy source. I designed a measuring system which is able to measure the friction losses of electro-pneumatic 5/2-way valves (monostable and bistable too). It is possible to choose between manual and automatic operation modes as well. In the automatic mode the system makes measurements in three different user-defined pressure levels. In the manual mode the measuring pressure can be set between 2-6 bars. An automatic evaluate program is also an important part of the created system. It gives the possibility of the fast evaluation of the saved data and it could be the base of a fast report generating application.